Chemical Characteristics Profile of Temulawak (Curcuma xanthorrhiza) Extract Processed Using a Miniplant-Scale Extractor with Variations in Temperature and Time - Bang, Jonathan Clarence Agathon; Victoria Kristina Ananingsih (JFCN: Journal of Food, Culinary, and Nutrition, 2025)
Temulawak (Curcuma zanthorrhiza) is a herbal plant native to Indonesia that contains bioactive compounds, such as curcuminoids, which possess antioxidant and anti-inflammatory properties. This study aims to examine the effect of varying extraction temperatures (70°C, 75°C, and 80°C) and extraction times (10, 20, 30, 40, 50, and 60 minutes) on the antioxidant activity and total phenol content of temulawak extract. The extraction was carried out using the conventional method, and the analysis was performed using the DPPH assay for antioxidant activity and the Folin-Ciocalteu method for total phenol content. The results showed that an extraction temperature of 75°C for 60 minutes yielded the highest antioxidant activity at 63.73%, with a phenol concentration of 63.56 mg GAE/g. At 70°C, antioxidant activity increased from 15.39% at 10 minutes to 60.84% at 60 minutes; however, this temperature was less efficient than 75°C. The extraction at 80°C resulted in the highest pH (7.95) but also increased the risk of bioactive compound degradation, as indicated by the increased variability in antioxidant activity. Overall, an extraction temperature of 75°C with an extraction time of 60 minutes provided optimal results, producing an extract with high antioxidant activity and total phenol content without significant degradation. This study provides valuable insights for optimizing the temulawak extraction process in the health and pharmaceutical industries.